The effect of trust based supply Chaın collaboratıon (scc) on supply Chaın performance (scp) and transactıon cost (tc) - Doğanay, Ahmet (My University, 2017)
ÖZETGünümüzde organizasyonlar, müşterilerinin olağanüstü ve dinamik olarak değişen gereksinimlerini karşılamak için daha fazla işbirlikleri kuruyorlar, çünkü talepkar ve rekabetçi bir ortamda başarılı bir şekilde tek başlarına rekabet edemiyorlar. Bu karmaşıklığa bir çözüm olarak, örgütler, tedarikçilerinin ve müşterilerinin kaynaklarını ve bilgilerini sonuna kadar kullanmak amacıyla tedarik zinciri işbirliğini kullanmaktadırlar.

ABSTRACTToday, organizations have been establishing more collaborations to meet their customers’ extraordinary and dynamically changing needs, because they can’t compete alone successfully in a demanding and competitive environment. They have been using supply chain collaboration to leverage the resources and knowledge of their suppliers and customers as a solution to this complexity.
Keywords: İşletme; Organizasyon; SUPPLY CHAIN PERFORMANCE; supply chain collaboration; TRANSACTION COST; TRANSACTION COST supply chain collaboration; Yönetim; Yönetim ve organizasyon